2021
DOI: 10.3389/fmars.2021.745083
|View full text |Cite
|
Sign up to set email alerts
|

Light Induced Changes in Pigment and Lipid Profiles of Bryopsidales Algae

Abstract: Bryopsidales (Chlorophyta) are cultured and consumed in several regions of the planet and are known for their high nutritional value and bioprospection potential, due to a high content of relevant polar lipids and polysaccharides. Among other characteristic features, these marine algae are known for possessing unique photosynthetic pigment-protein complexes and for the absence (in nearly all species investigated) of a functional xanthophyll cycle, a ubiquitous photoprotection mechanism present in most algae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In most eukaryotic algae the amount of glycosyl glycerides is much higher than the amount of other lipids such as phosphoglycerides or betaine lipids (Li‐Beisson et al, 2019). The lipid molecular species MGDG 18:3_16:3 was the most abundant MGDG species in A. acetabulum , C. tomentosum , and B. plumosa (Giossi et al, 2021; Rey et al, 2020). This lipid species was not identified in U. rigida growing in an integrated multi‐trophic aquaculture (IMTA) system (Lopes, Melo, et al, 2021); however, it was identified in U. rigida and other species of Ulva genus growing under laboratory conditions (Monteiro et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most eukaryotic algae the amount of glycosyl glycerides is much higher than the amount of other lipids such as phosphoglycerides or betaine lipids (Li‐Beisson et al, 2019). The lipid molecular species MGDG 18:3_16:3 was the most abundant MGDG species in A. acetabulum , C. tomentosum , and B. plumosa (Giossi et al, 2021; Rey et al, 2020). This lipid species was not identified in U. rigida growing in an integrated multi‐trophic aquaculture (IMTA) system (Lopes, Melo, et al, 2021); however, it was identified in U. rigida and other species of Ulva genus growing under laboratory conditions (Monteiro et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: DGDG, digalactosyl diacylglycerol; DGTS, diacylglyceryl-N,N,N-trimethyl homoserine; LPC, lyso phosphatidylcholine; MGDG, monogalactosyldiacylglycerol; MGMG, monogalactosyl monoacylglycerol; PC, phosphatidylcholine; PE, phosphatidylethanolamine; PG, phosphatidylglycerol; SQDG, sulfoquinovosyldiacylglycerol. Data of Codium tomentosum and Ulva rigida (Lopes, Melo, et al, 2021); data of Codium tomentosum and Bryopsis plumosa (Giossi et al, 2021); data of Acetabularia acetabulum (this study). [Color figure can be viewed at wileyonlinelibrary.com] found in thylakoid membranes (Li-Beisson et al, 2015).…”
Section: Lipidome Profilementioning
confidence: 88%
“…Thus, based on the shape of the PI molecule and its consequent physicochemical properties, a role of PI in extraplastidial membranes analogous to that of OGL in chloroplast membranes has been suggested (Gasulla et al, 2013). The substantial decrease (40%) in total lipid content, together with the large increase in PA and lysolipids (such as MGTS), suggests the activation of a process of lipid cleavage (Giossi et al, 2021) and cellular degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, alternatives for minimizing the negative impacts on human health and environment associated with the use of hazardous solvents such as chlorinated solvents are being considered in the lipid extraction of macroalgae. In particular, it has been used for the replacement of chloroform with less harmful solvents, such as dichloromethane [22,64] or methyl-tert-butyl ether. [65] After extraction, the total lipid content is usually determined by gravimetry.…”
Section: Lipidomics Analysis Based On Mass Spectrometry Approachesmentioning
confidence: 99%